Superhydrophilic properties of aluminum oxide nanofibers - Кадiр М. Ф.; Smirnov, V.; Алпысбаева , Б. Е.; Нұрман , Н. Б. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article considers structural properties of aluminum oxide nanofibers with superhydrophilic properties obtained in oxalic acid by single-stage electrochemical anodizing, whose structure differs from that of nanoporous aluminum oxide. The superhydrophilic properties of the obtained nanofibres were determined using an Ossila contact angle goniometer. It has been found that the duration of the anodisation process affects not only the nanostructure of the anodic oxide, but also the hydrophilic properties. The studies have shown that the contact angle of the nanofibres formed at 60 seconds of anodisation process decreases to 4.37 ◦ for 10 seconds and exhibits a superhydrophilic property.